1981
DOI: 10.1007/bf01851617
|View full text |Cite
|
Sign up to set email alerts
|

Urinary free amino acids pattern in protein-energy malnourished sudanese children

Abstract: The urinary free amino acid pattern in a morning urine sample of Sudanese children suffering from Kwashiorkor and marasmus were determined before and during the course of treatment up to the 2nd week. The urinary amino acid/total urinary N (3.62) was found to be almost constant for Kwashiorkor patients, while the mean for marasmic patients was found to be 27. The concentration of leucine, valine, phenylalanine, methylhistidine, lysine, hydroxylysine and beta-amino-isobutyric acid was elevated in marasmic child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It was demonstrated that kwashiorkor children have a high disturbance of amino acid metabolism with a consistent and significant reduction of plasma essential amino acids levels with individual amino acids affected to different degrees (60)(61)(62)(63)(64). Some non-essential amino acids remained at average levels (62) or might be kept at high level in the plasma of these children (61,63,64).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that kwashiorkor children have a high disturbance of amino acid metabolism with a consistent and significant reduction of plasma essential amino acids levels with individual amino acids affected to different degrees (60)(61)(62)(63)(64). Some non-essential amino acids remained at average levels (62) or might be kept at high level in the plasma of these children (61,63,64).…”
mentioning
confidence: 99%
“…It was demonstrated that kwashiorkor children have a high disturbance of amino acid metabolism with a consistent and significant reduction of plasma essential amino acids levels with individual amino acids affected to different degrees (60)(61)(62)(63)(64). Some non-essential amino acids remained at average levels (62) or might be kept at high level in the plasma of these children (61,63,64). In contrast, there was a particularly marked reduction of cysteine in erythrocytes and methionine in plasma (Grade A -Figure 3) and the flux of these amino acids during whole body protein turnover was compromised.…”
mentioning
confidence: 99%
“…Many newborns that are small for the ges tational age (small for date; SFD) show some clinical features indicating that prenatal nu trition is impaired [29], They also present some biochemical abnormalities which are characteristic of protein malnutrition [29], Numerous papers have been devoted to studies on plasma and urine amino acids in protein-energy malnutrition [3,4,10,11,13,18,21,23,27] and in experimental protein undernutrition [1,5,24,26] but these works have not always shown concordant results…”
Section: Introductionmentioning
confidence: 99%